Effect of enhanced homestead food production on anaemia among Cambodian women and children: A cluster randomized controlled trial. (31st May 2019) - Michaux, Kristina D.; Hou, Kroeun; Karakochuk, Crystal D.; Whitfield, Kyly C.; Ly, Sokhoing; Verbowski, Vashti; Stormer, Ame; Porter, Keith; Li, Kathy H.; Houghton, Lisa A.; Lynd, Larry D.; Talukder, Aminuzzaman; et al.
Abstract: There is inconsistent evidence on the efficacy of agriculture programmes at improving women and children's anaemia and nutritional status. The primary aim of this study was to evaluate the impact of a nutrition‐sensitive enhanced homestead food production (EHFP) programme on anaemia in women (18–45 years) and children (6–59 months) in rural Cambodia. Secondary outcomes were women's micronutrient status and women and children's anthropometry. In this cluster‐randomized controlled trial, 900 households from 90 villages (clusters) were randomized to either (a) home gardens and behaviour change communication (BCC) on nutrition, hygiene, women's empowerment, and marketing (EHFP); (b) home gardens plus fishponds and BCC (EHFP + F); or (c) control (no intervention). Haemoglobin concentration and anthropometry were measured in women and children at baseline and at 22 months. Venous blood samples were collected in a subset of women (n = 450) at baseline and at 22 months. Generalized linear mixed effect models with repeated measures were used to evaluate the difference across groups and the change from baseline to end of study. Ninety clusters, 552 women, and 754 children completed the trial. Compared with control, we found a statistically significant impact on anaemia prevalence in children (−14.0 percentage points; P = 0.02) and retinol binding protein concentrations in women (difference in difference: 0.34; P = 0.02) randomized to EHFP and EHFP + F groups, respectively. No other statistically significant effects on anaemia, nutritional biomarker concentrations, or anthropometry were observed. Future research is needed to examine longer term impacts of EHFP on anthropometry in women and children and into the nutritional causes of anaemia among children in Cambodia.